Kinematic and Thermodynamic Structures of Mesoscale Convective Systems During Heavy Rainfall in Greater Jakarta - Nuryanto, Danang Eko; Pawitan, Hidayat; Hidayat, Rahmat; Aldrian, Edvin (Makara Journal of Science, 2018)
A mesoscale convective system (MCS) is a large complex convective cloud system associated with a contiguous rainfall area that contributes significantly to heavy rainfall. This study analyzed the kinematic and thermodynamic structures of MCS during a heavy rainfall event. The MCSs that coincided with the heavy rainfall event and covered GJ occurred on January 17, 2013, 2014, and February 9, 2015. The three MCS cases were described from satellite observations over GJ during heavy rainfall. The main data consisted of satellite cloud top temperatures and national weather service soundings. We found a cloud shield with a temperature ≤ 221 K size and size less than 30,000 km2 at the mature stage of the MCS. Low moisture convection was unstable prior to MCS development. The warm moist air at 500–400 hPa could contribute to heavy rainfall above GJ. We suspect that the strong low-level convergence winds pro-duced an updraft, and high moist air led to a developing convective cloud. Themoist atmosphere on the third MCS was not always higher than others, but wind was low. These conditions caused the high intensity of heavy rainfall that oc-curred in GJ on the third MCS.